2012
DOI: 10.1038/onc.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

YAP induces malignant mesothelioma cell proliferation by upregulating transcription of cell cycle-promoting genes

Abstract: Malignant mesothelioma (MM) shows frequent inactivation of the neurofibromatosis type 2 (NF2) --tumor-suppressor gene. Recent studies have documented that the Hippo signaling pathway, a downstream cascade of Merlin (a product of NF2), has a key role in organ size control and carcinogenesis by regulating cell proliferation and apoptosis. We previously reported that MMs show overexpression of Yes-associated protein (YAP) transcriptional coactivator, the main downstream effector of the Hippo signaling pathway, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
201
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 35 publications
20
201
0
2
Order By: Relevance
“…Interestingly, in synovial sarcoma, FOXM1 levels appear to be less uniform, suggesting that they use alternate mechanisms of proliferation control. The Oncomine coexpression analysis tool identified genes whose expression paralleled FOXM1 in STS, and the top 40 genes were compared with established or potential YAP targets identified in the literature (6,16,29) and a microarray dataset of YAP-regulated genes in human malignant mesothelioma cells (10). Of the top 40 genes coexpressed with FOXM1 in the Detwiller et al database, 13 are also putative YAP targets ( Fig.…”
Section: Injection We Minimizedmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, in synovial sarcoma, FOXM1 levels appear to be less uniform, suggesting that they use alternate mechanisms of proliferation control. The Oncomine coexpression analysis tool identified genes whose expression paralleled FOXM1 in STS, and the top 40 genes were compared with established or potential YAP targets identified in the literature (6,16,29) and a microarray dataset of YAP-regulated genes in human malignant mesothelioma cells (10). Of the top 40 genes coexpressed with FOXM1 in the Detwiller et al database, 13 are also putative YAP targets ( Fig.…”
Section: Injection We Minimizedmentioning
confidence: 99%
“…For the first time, to our knowledge, we show that YAP interacts with the forkhead box transcription factor FOXM1 to coregulate critical components of sarcomagenesis, specifically in fibrosarcoma, undifferentiated pleomorphic sarcomas, and liposarcomas. (8)(9)(10)(11). Recent studies have revealed that mutations in the Hippo pathway are more common than previously thought (8,12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, molecular analysis of MPM cells revealed several molecules implicated in the development of MPM. In particular, inactivation of the NF2/merlin signaling pathway caused by loss of NF2/merlin, LATS2 or up-regulation of YAP1 (Mizuno et al 2012) in MPM cells. In addition, inactivation of p16/ink4a, inactivation of tumor suppressor PTEN, and somatic mutations of BRCA 1-associated protein-1 (BAP1) were also reported in MPM cells (Kratzke et al 1995;Opitz et al 2008;Bott et al 2011;Testa et al 2011).…”
Section: Discussionmentioning
confidence: 99%